Evidence for improved systemic and local vascular function after long‐term passive static stretching training of the musculoskeletal system. (1st July 2020) - Bisconti, A. V.; Cè, E.; Longo, S.; Venturelli, M.; Coratella, G.; Limonta, E.; Doria, C.; Rampichini, S.; Esposito, F.
Abstract : Key points: Vascular function and arterial stiffness are important markers of cardiovascular health and cardiovascular co‐morbidity. Transitional phases of hypoemia and hypermia, with consequent fluctuations in shear rate, occuring during repetitive passive stretching adminstration (passive stretching training) may constitute an effective stimulus to induce an amelioration in vascular function, arterial stiffness and vascular remodelling by improving central and local blood flow control mechanisms. Vascular function, arterial stiffness and vascular remodelling were evaluated before and after 12 weeks of passive stretching training and after 6 weeks from training cessation, in the femoral, popliteal (treated with stretching), and brachial arteries (untreated) of both sides. After passive stretching training, vascular function and arterial remodelling improved, and arterial stiffness decreased in all the arteries, suggesting modifications of both central and local blood flow control mechanisms. Passive stretching‐induced improvements related to central mechanisms seemed to have a short duration, as they returned to pre‐training baseline within 6 weeks from training cessation, whereas those more related to a local mechanism persisted in the follow‐up. Abstract: Acute passive stretching (PS) effects on blood flow ( Q ̇ ), shear rate ( Y ̇ ), and vascular function in the feeding arteries of the stretched muscle have been extensively investigated; however, few data are available on vascular adjustments induced by long‐term PS training. We investigated the effects of PS training on vascular function and stiffness of the involved (femoral and popliteal) and uninvolved (brachial) arteries. Our hypothesis was that PS‐induced changes in Q ̇ and Y ̇ would improve central and local mechanisms of Q ̇ control. Thirty‐nine participants were randomly assigned to bilateral PS ( n = 14), monolateral PS ( n = 13) or no PS training ( n = 12). Vascular function was measured before and after 12 weeks of knee extensor and plantar flexor muscles' PS training by single passive limb movement and flow‐mediated dilatation (FMD). Central (carotid‐femoral artery PWV, PWVCF ) and peripheral (carotid‐radial artery PWV, PWVCR ) arterial stiffness was measured by pulse‐wave velocity (PWV), together with systolic (SBP) and diastolic (DBP) blood pressure. After PS training, increases of 30%, 25% and 8% ( P < 0.05) in femoral Δ Q ̇, popliteal and brachial artery FMD%, respectively, occurred in both PS training groups. A decrease in PWVCF, PWVCR, SBP and DBP (−25%, −17%, −4% and −8%, respectively; P < 0.05) was noted. No changes occurred in controls. Vascular function improved and arterial stiffness reduced in the arteries involved and uninvolved with PS training, suggesting modifications in both central and local Q ̇ control mechanisms. PS‐induced improvements had a short duration in some of vascular function parameters, as they returned to baseline within 6 weeks of PS training cessation. Key points: Vascular function and arterial stiffness are important markers of cardiovascular health and cardiovascular co‐morbidity. Transitional phases of hypoemia and hypermia, with consequent fluctuations in shear rate, occuring during repetitive passive stretching adminstration (passive stretching training) may constitute an effective stimulus to induce an amelioration in vascular function, arterial stiffness and vascular remodelling by improving central and local blood flow control mechanisms. Vascular function, arterial stiffness and vascular remodelling were evaluated before and after 12 weeks of passive stretching training and after 6 weeks from training cessation, in the femoral, popliteal (treated with stretching), and brachial arteries (untreated) of both sides. After passive stretching training, vascular function and arterial remodelling improved, and arterial stiffness decreased in all the arteries, suggesting modifications of both central and local blood flow control mechanisms. Passive stretching‐induced improvements related to central mechanisms seemed to have a short duration, as they returned to pre‐training baseline within 6 weeks from training cessation, whereas those more related to a local mechanism persisted in the follow‐up.